Steps towards the Integration of the Gender and Sex Dimension in R&I: The Case of a Public University - Carina Jordão; Sara Diogo (MDPI AG, 2022)
Gender equality has been placed at the centre of European research policy recently. The inclusion of gender and sex considerations into research and innovation (R&I) is an essential factor for scientific excellence and a key requirement for producing knowledge that can benefit society as a whole. However, the adoption of a gender/sex dimension is still a problematic issue in several Research Performance Organisations (RPOs) of European Union (EU) countries. Through the experience of implementing a gender equality plan (GEP) within the scope of a Horizon 2020 (H2020) project at a public Portuguese university (PPU), this study aims to explore the EU policies' impact on the integration of the gender dimension in research, considering both institutional policies and scientific outputs. To achieve the purpose of the study, a mixed approach that combines a qualitative analysis of institutional documents and data collected through interviews with a quantitative analysis of secondary data is used. The implementation of the H2020 project brought the issue of gender inequality to the institutional agenda of the PPU under study and the formalisation of the GEP marked a transition point towards an integrated and intersectional approach that embraces gender dimension concerns in R&I. This transition coincided with a period characterised by an increase in the scientific outputs incorporating the 'gender/sex dimension', which may highlight the importance of European policies in stimulating and accelerating the introduction of the gender dimension in scientific practices in RPOs.